Women’s Decision Making Power and Human Development : Evidence from Pakistan - Hou, Xiaohui (2012)
When deciding who should receive welfare benefits with the aim to increase household well-being, it is necessary to understand the effects of the distribution of power within the households at which the aid is directed. Two primary household models have been used to study intra-household bargaining and decision making: the unitary model and the collective model. The unitary model seems to fit Pakistan's context because the prevailing traditional culture positions the male head as the household decision maker. However, using a set of direct measures of decision-making power from the Pakistan Social and Living Standard Measurement Survey, this study finds that even in a country where men seem to have more power than women, the collective household bargaining model applies. This study also finds that, in Pakistan, when women have more decision-making power at home, households tend to spend more on women's preferred goods (such as clothing and education), family members eat more non-grain food items, and children, particularly girls, are more likely to be enrolled in school.